Evaluation of non-Gaussian model-based diffusion-weighted imaging in oral squamous cell carcinoma: comparison with tumour functional information derived from positron-emission tomography. Issue 5 (May 2020) - Shima, T.; Fujima, N.; Yamano, S.; Kudo, K.; Hirata, K.; Minowa, K.
Abstract : Aim: To evaluate and compare diffusion-weighted imaging (DWI) parameters derived from a non-Gaussian fitting model and positron-emission tomography (PET) parameters derived from 18 F-fluoromisonidazole-PET (FMISO-PET) in patients with oral squamous cell carcinoma (OSCC). Materials and methods: Primary sites were evaluated prospectively in 18 patients. DWI was performed using six b-values (0–2, 500). Diffusion-related parameters of kurtosis value (K), the kurtosis-corrected diffusion coefficient (DK ), diffusion heterogeneity (α), distributed diffusion coefficient (DDC), the slow diffusion coefficient (Dslow ), and the apparent diffusion coefficient (ADC) were calculated from four diffusion-fitting models. Maximal standardised uptake values (SUVmax ), mean standardised uptake values (SUVmean ), and the tumour-to-muscle ration (TMR) of the SUV value were calculated for FMISO-PET. Spearman's correlation coefficient was used to evaluate the correlation between each non-Gaussian diffusion model parameters and PET parameter. Results: There was moderate correlation between FMISO-PET SUVmax and Dslow ( ρ= –0.45, p= 0.06). In addition, there was good correlation between TMRmax and five non-Gaussian diffusion model parameters (K: ρ= 0.65, p= 0.004, DK : ρ= −0.72, p= 0.0008, DDC: ρ= −0.75, p= 0.0003, ADC: ρ= −0.74, p= 0.0005, and Dslow : ρ= −0.65, p= 0.003), and between TMRmean and five non-Gaussian model parameters (K: ρ= 0.64, p= 0.005, DK : ρ= −0.61, p= 0.007, DDC: ρ= −0.63, p= 0.005, ADC: ρ= −0.61, p= 0.007, and Dslow : ρ= −0.56, p= 0.015). Conclusion: Non-Gaussian diffusion model parameters can be related to tumour hypoxia. Highlights: Not only ADC but advanced diffusion model parameters correlated with PET parameters. Dslow sufficiently correlated with FMISO-PET SUVmax, TMRmax, TMRmean . Diffusion heterogeneity parameters showed correlations with FMISO-PET parameters.